2010
DOI: 10.1073/pnas.1006897107
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a high-affinity Gag recognition structure mediating packaging of a retroviral RNA genome

Abstract: All retroviral genomic RNAs contain a cis-acting packaging signal by which dimeric genomes are selectively packaged into nascent virions. However, it is not understood how Gag (the viral structural protein) interacts with these signals to package the genome with high selectivity. We probed the structure of murine leukemia virus RNA inside virus particles using SHAPE, a high-throughput RNA structure analysis technology. These experiments showed that NC (the nucleic acid binding domain derived from Gag) binds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 48 publications
(56 reference statements)
8
92
0
Order By: Relevance
“…Experiments with minor RNA-specific variations have been reported for the TPP riboswitch (Steen et al 2012), a retroviral genome signaling domain (Gherghe et al 2010;Grohman et al 2011), ribosomal RNAs McGinnis et al 2012), and long viral RNAs Watts et al 2009;Gherghe et al 2010). The key new feature is that all experiments are now resolved in two capillaries.…”
Section: Shape Datamentioning
confidence: 90%
“…Experiments with minor RNA-specific variations have been reported for the TPP riboswitch (Steen et al 2012), a retroviral genome signaling domain (Gherghe et al 2010;Grohman et al 2011), ribosomal RNAs McGinnis et al 2012), and long viral RNAs Watts et al 2009;Gherghe et al 2010). The key new feature is that all experiments are now resolved in two capillaries.…”
Section: Shape Datamentioning
confidence: 90%
“…These results support the hypothesis that recognition of one dimeric RNA by Gag is a key point of viral RNA encapsidation. Recent advances shed light on how Gag recognizes dimeric RNA; for example, studies of MLVs have revealed that dimerization of the viral RNA exposes high-affinity Gag binding sites to allow the initiation of RNA packaging (49)(50)(51). Studies in HIV-1 have also identified structural elements important in dimerization, Gag binding, and packaging (17,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…A model for the switch between translation and packaging has been proposed based on NMR spectroscopy data showing that the DIS loop of SL1 folds back and interacts with an upstream region in the viral RNA, thereby preventing dimerization of SL1 and promoting translation (Lu et al 2011a). In MLV, dimerization of the gRNA exposes high-affinity binding sites for the NC domain of Gag (D'Souza and Summers 2004;Gherghe et al 2010;Miyazaki et al 2010), suggesting that packaging and Gag binding to ψ are coordinated with dimerization. In HIV-1, a 159-nt "core encapsidation signal" was recently described that binds NC with similar affinity as the full-length 5 ′ leader sequence (Heng et al 2012).…”
Section: Thementioning
confidence: 99%